HUBUNGAN EXPLOSIVE POWER TUNGKAI DENGAN HASIL LOMPAT JAUH SISWA KELAS V SDN 014 RAMBAH - Muhammad Saleh (JURNAL PENDIDIKAN ROKANIA, 2018)
The research conducted on the students of grade V SD 014 Rambah Rokan Hulu, that is to know the extent of relationship between exsplosive power of leg muscle to long jump results obtained t count = 0,615, t table = 0,396 thereby can be drawn a conclusion there is explosive power of leg muscle with the results of long jump students V SD 014 Rambah Rokan Hulu.